What is immeasurable make measurable with artificial intelligence (measurements & artificial intelligence). (December 2021) - Taymanov, Roald; Sapozhnikova, Kseniia; Prokopchina, Svetlana
Abstract: The analogy between biological evolution and development of measurement techniques is analysed in the paper. It follows from this analogy that at present, in order to achieve measurement trustworthiness, to apply measuring instruments provided by the functions of metrological self-check/self-validation and artificial intelligence is necessary. Taking into consideration extending the measurand spectrum into the field of multidimensional ones, the authors of the paper show the tasks, solution to which is particularly efficient with artificial intelligence application. The necessity is noted to issue national and international standards related to intelligent measuring instruments and systems with artificial intelligence. The period of validity for such standards should be rather short.